1987
DOI: 10.1007/bf00350438
|View full text |Cite
|
Sign up to set email alerts
|

The value of computed tomography in patients with mucopolysaccharidosis

Abstract: Cranial computed tomography (CT) was performed on 11 cases of mucopolysaccharidosis (MPS) IVA (Morquio syndrome). Our results suggest that although the patients may have normal intelligence CT changes may be seen with increasing age. In two cases white matter low density was found and in a third there was gross dilatation of the ventricles, basal cisterns and subarachnoid space. Nine other patients with various types of mucopolysaccharidosis also had cranial CT performed and in general those types associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…In all cases where the patient was alive at the time of the study, the diagnosis was confirmed by the appropriate enzyme assay. Clinical, biochemical, mutation analysis and radiological findings on many of the patients have already been described (Nelson 1986;Nelson and Grebbell 1987;Nelson and Kinirons 1988;Nelson and Thomas 1988;Nelson and Carson 1989;Kinirons and Nelson 1990;Nelson et al 1990; Thomas et al 1991;Nelson et al 1993;Yamada et al 1997).…”
Section: John Nelsonmentioning
confidence: 89%
“…In all cases where the patient was alive at the time of the study, the diagnosis was confirmed by the appropriate enzyme assay. Clinical, biochemical, mutation analysis and radiological findings on many of the patients have already been described (Nelson 1986;Nelson and Grebbell 1987;Nelson and Kinirons 1988;Nelson and Thomas 1988;Nelson and Carson 1989;Kinirons and Nelson 1990;Nelson et al 1990; Thomas et al 1991;Nelson et al 1993;Yamada et al 1997).…”
Section: John Nelsonmentioning
confidence: 89%
“…7 The first neuroradiologic studies in MPS were performed with the use of x-ray CT and led to the identification of nonspecific imaging features, most prominent of which were the demonstration of low-attenuation white matter areas and the presence of ventricular and subarachnoid space dilation. 8 The identification of white matter changes in the brain of patients with MPS led to the first MR imaging studies, because this imaging technique is undoubtedly the most sensitive method and represents, currently, the primary imaging technique for the detection of brain and spinal abnormalities in patients with MPS.…”
Section: Neuropathologic and Ct Neuroimaging Studiesmentioning
confidence: 99%
“…In Table I, the main clinical features of MPSs are listed including reference to the association with MR. The first neuroradiological studies of the CNS, using Computerized Tomography have led to the identification of cerebral alterations that are not specific for MPSs; such as low density areas in the white matter (WM) and ventricular and subarachnoid space dilation [Watts et al, 1981; Nelson and Grebbell, 1987]. Further studies proved that Magnetic Resonance Imaging (MRI) is the primary imaging modality for the detection of WM abnormalities in patients with MPSs [Afifi et al, 1990].…”
Section: Introductionmentioning
confidence: 99%